2007
DOI: 10.1002/hed.20700
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chemoradiotherapy with weekly paclitaxel and carboplatin for locally advanced head and neck cancer: Long‐term follow‐up of a Brown University Oncology Group Phase II Study (HN‐53)

Abstract: Concurrent paclitaxel, carboplatin, and RT for advanced head and neck cancer results in high complete response rates. Long-term follow-up has revealed the curative potential of this regimen, though the doses used resulted in unacceptable toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 24 publications
3
21
0
2
Order By: Relevance
“…The combination of platinum and paclitaxel has been tested by several groups in phase II studies. Because of severe mucosal toxicity reported by Chogule et al [6], the recommended weekly paclitaxel dose was adjusted from the initial 60 mg/m 2 to 40 mg/m 2 together with carboplatin weekly AUC 1 and conventionally fractionated radiotherapy. The authors observed promising rates of survival and locoregional control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of platinum and paclitaxel has been tested by several groups in phase II studies. Because of severe mucosal toxicity reported by Chogule et al [6], the recommended weekly paclitaxel dose was adjusted from the initial 60 mg/m 2 to 40 mg/m 2 together with carboplatin weekly AUC 1 and conventionally fractionated radiotherapy. The authors observed promising rates of survival and locoregional control.…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel -representative of the second generation chemotherapy -has been used in SCCHN single-agent [7,14] or platinum-based radiochemotherapy protocols [2,6,8,15,22,25]. Current treatment strategies often use hyperfractionated or hyperfractionated-accelerated radiotherapy protocols to enhance efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Chougule et al [18] postulated curative impact using CarboTaxol with RT with lower rates of toxicity than using cisplatin. However, despite this, they found that the doses used (carboplatin AUC1 and paclitaxel 60 mg/m²) led to high cumulative toxicity: 37 from 41 patients (90%) developed grade 3/4 mucositis.…”
Section: Discussionmentioning
confidence: 99%
“…Most institutions use cisplatin as their gold-standard chemotherapeutic agent. Nevertheless, several studies describe limited experience with CarboTaxol and RT for SCCHN [18,19,20,21,40,41]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation